LEGAL SPECIFICITIES AND PROBLEMS IN LATVIAN PORTS` REGULATIONS - Dreiblathens, Aldis (Administrative and Criminal Justice, 2015)
The importance and the great potential for improvements for Latvian ports are directly linked to its geographic position, being located between Europe and Asia. This is why due to the essential role it plays in maritime, Latvian ports cannot be excluded from the international law of the Sea. A prerequisite for maritime safety insurance in ports is the development of maritime security and port legal acts in accordance with the modern international law and regulations. Operations of the major ports in Latvia as well as the maritime safety in ports are controlled and regulated by binding rules issued by municipalities. This study focuses on examining the norms included in the port regulations as well as to what extent ports are capable of ensuring navigation safety in ports according to the legal framework. The study also compares and analyses the differences in legal frameworks in the major Latvian ports, their solution in improving the regulations as well as suggesting a possible way on how the port rulemaking body should be structured.